(untitled) (Journal of the College of Basic Education, 2022)
Idioms can be considered part of everyday language and languages are full of colour –related idioms and expressions which refer to ideas that lie beyond the literal extensions of dictionary meaning .This study aims at investigating difficulties encountered by EFL learners in learning the communicative force of idiomatic expressions with special reference to colour idiomatic expressions. The researcher has been adopted a pragmatic approach for her analysis Two instruments have been used for collecting data; namely ,recognition and production test given to the fourth year students of English /Al- Mustansiriya University /college of Arts /department of English. The sample consists of 40 students. The results showed that students get confused in using colour idiomatic expressions, and face problems in figuring out the communicative force of these expressions. Moreover, it is found that the majority of errors committed by the participants through the production test are due to the fact that Iraqi EFL learners unacquainted with such idioms. Additionally, it is observed that Iraqi EFL learners have committed fewer errors in the recognition test due to the fact that they have somehow pragmatic competence and background knowledge regarding these idioms. Consequently, Iraqi EFL students should be recommended to develop their language skills give much more awareness, attention and practice to idiomatic expressions.